1999
DOI: 10.7164/antibiotics.52.256
|View full text |Cite
|
Sign up to set email alerts
|

Novel Naphthoquinones from a Streptomyces sp.

Abstract: Cdc25A assay-guided fractionation of a fermentation broth derived from a Streptomyces sp. resulted in the isolation of four novel naphthoquinones 1~4. Structures of these compounds were deduced by NMRand mass spectrometry. Two of them, 3 and 4, incorporate a modified cysteine residue which is observed for the first time in this class of natural products. Naphthoquinones 1~4 showed weak activity against cdc25A phosphatase.Cyclin/cdk (cyclin-dependent kinase) complexes serve as regulatory checkpoints for cell cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…Despite the large number of rifamycins reported, either natural or synthetic, the amino group is mostly found at the C-2 position of the naphthoquinone nucleus. Naturally occurring 3-aminonaphthoquinones, although rare, have been reported previously. , This can explain the presence, in this case, of compound 3 (3-amino) among compounds 1 , 2 , 4 , and 5 .…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…Despite the large number of rifamycins reported, either natural or synthetic, the amino group is mostly found at the C-2 position of the naphthoquinone nucleus. Naturally occurring 3-aminonaphthoquinones, although rare, have been reported previously. , This can explain the presence, in this case, of compound 3 (3-amino) among compounds 1 , 2 , 4 , and 5 .…”
Section: Resultssupporting
confidence: 56%
“…In conclusion, compounds 1 – 5 are 2- or 3-amino-1,4-naphthoquinones; however, they have the important core present in several biologically important natural products such as rifamycins, salinisporamycin, and a Cdc25A inhibitor …”
Section: Resultsmentioning
confidence: 99%
“…The first is 524, the second 525 then 526 and its epimer. 182 A patent 183 describes a product of the micro-organism Streptomyces melanovinaceus as being antitumourous. Designated DX-512-1 it was found to be a mixture of products whose structure incorporates 527.…”
Section: Miscellaneous Alkaloidsmentioning
confidence: 99%
“…Sulfur incorporation can significantly expand the structural diversity and bioactivities of many naturally occurring molecules ( Hai et al, 2021 ), many sulfur-containing natural products, such as penicillin and ixabepilone, have been approved for clinic therapy. However, bacterial sulfur-containing aromatic polyketides are relatively rare, with only a few examples reported over the past decades ( Etoh et al, 1987 ; Ohta et al, 1987 ; Rohr and Zeeck, 1987 ; Miyata et al, 1992 ; Aoyama et al, 1993 ; Carney et al, 1997 ; Kulanthaivel et al, 1999 ; Sasaki et al, 2010 ; Taguchi et al, 2013 ; Wang et al, 2013 ; Woo et al, 2013 ; Taguchi et al, 2015 ; Bilyk et al, 2016 ; Che et al, 2016 ; Xie et al, 2016 ; Nakashima et al, 2017 ; Matsuo et al, 2019a ; Bae et al, 2019 ; Matsuo et al, 2019b ; He et al, 2019 ; Fang et al, 2020 ; Cao et al, 2021 ). Amongst these reports, naquihexcin A could inhibit the proliferation of the adriamycin resistant human breast cancer ( Che et al, 2016 ); nanaomycin K showed an inhibitory effect on the epithelial-mesenchymal transition ( Matsuo et al, 2019a ); and naquihexcin E exhibited a notable anti-HIV activity ( He et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%